2009
DOI: 10.1002/jmv.21482
|View full text |Cite
|
Sign up to set email alerts
|

Absence of genotypic drug resistance and presence of several naturally occurring polymorphisms of human immunodeficiency virus‐1 CRF06_cpx in treatment‐naive patients in Estonia

Abstract: All non-B HIV-1 subtypes and circulating recombinant forms (CRFs) are characterized by several polymorphisms in protease (PR) region. In addition, in recent years the increasing use of antiretroviral treatment (ART) has rapidly raised the spread of transmitted drug resistance. We aimed to determine the presence of naturally occurring polymorphisms and transmitted drug resistance mutations (DRMs) in ART naïve HIV-1-positive subjects in Estonia. A total of 115 drug-naive HIV-1-infected subjects (mean age 27 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 29 publications
1
11
0
1
Order By: Relevance
“…The HIV-1 subtypes were determined by phylogenetic analyses which revealed the monophyletic pattern of the V3 region of HIV-1 which is consistent with our previous studies 16, 17 . Of the sequenced viruses, 93.8% belonged to CRF06_cpx.…”
Section: Resultssupporting
confidence: 87%
“…The HIV-1 subtypes were determined by phylogenetic analyses which revealed the monophyletic pattern of the V3 region of HIV-1 which is consistent with our previous studies 16, 17 . Of the sequenced viruses, 93.8% belonged to CRF06_cpx.…”
Section: Resultssupporting
confidence: 87%
“…Thus, we would expect countries with higher number of prevalent cases to be more likely to provide spillovers to other countries. To examine whether our analyses is consistent with this expectation, we estimated the country-specific number of HIV subtype B infections by multiplying the total number of people living with HIV-1 per country until 2011, based on the UNAIDS figures (www.unaids.org), by the percentage of subtype B in each country (Abecasis et al, 2013, Avi et al, 2009, Balode et al, 2012, Ciccozzi et al, 2005, Ivanov et al, 2013, Saad et al, 2006, Stanojevic et al, 2012, Ustina et al, 2001). We then examined the association between the number of HIV subtype B infections per country/region and the number of countries that each country/region exported viral strains in analysis (4) by running a regression analysis.…”
Section: Resultsmentioning
confidence: 90%
“…53,54 Recent pol region analysis showed that the subtype structure of the Estonian HIV epidemic remained unchanged up to 2008. [56][57][58] Drug resistance mutations of HIV were investigated in Estonian treatment naive populations in 2005-2006 and 2008. [56][57][58] These studies indicated that CRF06_cpx and its recombinant forms with subtypes A1 possess several naturally occurring polymorphisms in the protease region (K14R, M36I, H69K, and L89M), also characteristic to other non-B subtype epidemics.…”
Section: Hiv Molecular Epidemiologymentioning
confidence: 99%